The effect of culture on trade over time: New evidence from the GLOBE data set - Jonas Frank (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
In this essay I use the GLOBE research study by House et al. (2013) as a proxy for measuring cultural distance. Unlike other studies, GLOBE introduces nine cultural dimensions and focuses exclusively on managers, allowing for a distinct glimpse into the values of people actually making trade decisions. I make use of a state-of-the-art PPML approach using data on international trade flows together with intra-national trade flows (Yotov, 2012) and a comprehensive set of fixed effects to consistently estimate a gravity equation using a panel from 1995 to 2004. I distinguish between different industries by following the goods classification introduced by Rauch (1999). The results show that cultural differences indeed effect trade values differently over time, but their size and impact depends on the chosen measure of cultural distance and on the industry classification.
urn:nbn:de:bsz:100-opus-15066
Keywords: F14; M14; 330; Cultural Distance; International Trade; Panel Gravity Model; PPML